2018
DOI: 10.1007/s40123-018-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Atropine Penalization Versus Occlusion Therapies for Unilateral Amblyopia after the Critical Period of Visual Development: A Systematic Review

Abstract: IntroductionAmblyopia therapy appears to be most effective in children under the age of 7 years, but results from randomized control trials (RCTs) have shown that occlusion therapy and/or atropine penalization therapy may improve visual acuity in an older age group. Which of these two therapies is the most effective with fewer adverse effects in an older age group has not yet been agreed upon.MethodsWe systematically searched the literature for RCTs that compared atropine penalization therapy and occlusion the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…From historical research, three systematic reviews have been conducted to compare the conventional patching therapy with atropine penalization; both of the results suggested that atropine was as effective as patching in improving visual acuity [15,52,53]. In a head-to-head meta-analysis, there was no difference between part-time and full-time occlusion [14].…”
Section: Discussionmentioning
confidence: 99%
“…From historical research, three systematic reviews have been conducted to compare the conventional patching therapy with atropine penalization; both of the results suggested that atropine was as effective as patching in improving visual acuity [15,52,53]. In a head-to-head meta-analysis, there was no difference between part-time and full-time occlusion [14].…”
Section: Discussionmentioning
confidence: 99%
“…20 23-28 A number of randomised controlled trials (RCTs) over the past two decades have evaluated the efficacy of monocular (eg, patching, atropine and Bangerter filters) and binocular treatments for improving amblyopic eye VA. Comparisons of vision-based treatments for patients with amblyopia have been examined in systematic reviews comparing patching against atropine [29][30][31] or binocular treatments against patching. [32][33][34] Only one review 35 included a meta-analysis, which was limited to two studies and two treatments.…”
Section: Key Messagesmentioning
confidence: 99%
“…It is of importance to monitor the child by both clinician and caregiver to assess progress. Penalization can be employed as alternative to patching, and it involves the use of atropine eye drops to blur images in the better eye, thus encouraging the child to use the so-called weaker eye [40].…”
Section: Amblyopiamentioning
confidence: 99%